Pembekalan Teknik Kewirausahaan melalui Brainstorming pada Siswa Sekolah Dasar Negeri 8 Limboto Barat - Ardiyanto Saleh Modjo (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
State Elementary School 8 Limboto Barat, located in Yosonegoro Village, Limboto Barat Subdistrict, has significant potential for fostering entrepreneurship among its students. The total number of students, 196, necessitates early entrepreneurship education to create job opportunities and independence in the future. One of the essential aspects of this education is entrepreneurship techniques, starting with the brainstorming method. To provide this training, the school invited lecturers from Gorontalo State University. In the initial stage of this training, 70 students were selected by State Elementary School 8 Limboto Barat to participate. The brainstorming method was chosen to help students effectively generate business ideas, understand, and skillfully use brainstorming to develop business concepts. The aim is to shift their mindset from relying on formal employment to becoming independent job creators. The results of the brainstorming training showed that 70 students, divided into 14 groups, achieved scores ranging from a high of 96 to a low of 89. According to the assessment standards, all groups, or 100%, met the criteria for excellence in understanding entrepreneurship concepts and generating innovative business ideas. The conclusion is that this training is effective, as 70 students successfully mastered entrepreneurial brainstorming, which includes understanding entrepreneurship, generating business ideas, selecting several business ideas, choosing one business idea, and skillfully using brainstorming techniques.